Biofilms formed by microbiota recovered from fresh produce: Bacterial biodiversity, and inactivation by benzalkonium chloride and enterocin AS-48. (April 2017) - Grande Burgos, M José; Pérez-Pulido, Rubén; Gálvez, Antonio; Lucas, Rosario
Abstract: Microbiota recovered from fresh produce (Romaine lettuce, endives and cucumbers) was allowed to form biofilms on stainless steel coupons. The formed biofilms were treated with benzalkonium chloride (BC) at three different concentrations (0.01, 0.1, and 1.0 g/l), enterocin AS-48 (50 μg/ml) and combinations of BC and enterocin AS-48. The single treatment with bacteriocin had no effect on viability of sessile bacteria. A high concentration of BC (1.0 g/l) was required to achieve 4.1 logs reduction of viable cell counts. The combination of BC (1.0 g/l) and enterocin AS-48 reduced viable cell counts below detectable levels. High-throughput sequencing analysis revealed that the formed biofilms were composed mainly by Proteobacteria of the genera Pseudomonas and Stenotrophomonas . Treatments with enterocin AS-48 and BC at sub-inhibitory concentrations only induced minor changes in the relative abundance of the different bacterial groups associated with biofilms. Highlights: Microbiota from fresh produce formed biofilms on stainless steel coupons. Biofilms were highly resistant to benzalkonium chloride (BC). The combination of BC and enterocin AS-48 improved microbial inactivation in biofilms. Proteobacteria (mainly Pseudomonas and Stenotrophomonas ) were the predominant group in biofilms. Sublethal treatments with BC + AS-48 did not significantly change microbial composition of biofilms.